Exile and Election: The Case for Barring Exiled Leaders from Contesting in National Elections - Fizza Batool (Washington University Global Studies Law Review, 2017)
During the twentieth century, the world witnessed a series of regime changes. Dictatorships, military coups, and fascist governments were rejected in favor of democratic values and principles. This change in governance seems to have continued into the twenty-first century, albeit with some major challenges in the implementation of a democratic system in States. One of the more alarming trends has been exiled leaders returning to their State to contest national elections despite facing serious criminal charges. This causes the developing democratic State’s legitimacy of governance, free and fair elections, accountability, and transparency to be threatened. Fragile States struggling to implement democracy cannot do so without a stable elections system. The ability of exiled leaders to participate in elections when they have not been held accountable for serious offenses would greatly undermine the establishment of this system. To prevent this harm, international and domestic laws must begin to play a stronger role in addressing this problem. Pakistan is a State which highlights this troubling trend. This article will explore the policies supporting a restriction on leaders from participating in national elections until their criminal charges have been resolved. It will first present a brief historical gloss on exile and its formal use by world leaders. Next, in order to demonstrate the significance of utilizing both international and domestic laws, international electoral standards and Pakistan’s electoral standards will be assessed. In addition, the implications of this trend will be discussed by contrasting the exile of three highly controversial political leaders with cases in present-day Pakistan. Finally, the role of domestic and international laws, courts, and host States will be examined in relation to this proposition.
Keywords: national elections; regime change; dictator; military coup; democracy; exile; contested elections; head of state; Pakistan; Mohammad Reza Shah Pahlavi; Ferdinand Marcos; Idi Amin; criminal law; international criminal law